Informal and implicit learning: concepts, communalities and differences - Straka, Gerald A. [Verfasser] (My University, 2010)
"Informal learning and its validation has become a major issue in European and national education policy, raising the following questions. May learning be constituent for political action? Is learning the focus of validation? Is informality a feature of learning? Is implicit learning solely related to informality? To give answers, a general learning concept is introduced, focusing on the acting individual in socioculturally shaped environments. Using this concept, learning is exclusively realised by the individual and therefore may not be a constituent element of political actions. Learning outcomes, not learning, are validated. Implicit learning is not only related to informality, and formality is not a feature of learning. From this perspective, 'informality' and the opposite 'formality' have to be located in conditions external to the learner, characterised by the 'extent of educational arrangement', 'certification' and 'approved public regulations'. Consequently, the term 'informal learning' is triggering inappropriate associations." (Autorenreferat, BIBB-Doku)
Keywords: L 2.1.1 Informelles Lernen; T 2.2 Lerntheorien; Lernen; Informelles Lernen